Operational Amplifiers Theory and Design - Huijsing, Johan (Springer International Publishing : Imprint: Springer, 2017)
This proven textbook guides readers to a thorough understanding of the theory and design of operational amplifiers (OpAmps). The core of the book presents systematically the design of operational amplifiers, classifying them into a periodic system of nine main overall configurations, ranging from one gain stage up to four or more stages. This division enables circuit designers to recognize quickly, understand, and choose optimal configurations. Characterization of operational amplifiers is given by macro models and error matrices, together with measurement techniques for their parameters. Definitions are given for four types of operational amplifiers depending on the grounding of their input and output ports. Many famous designs are evaluated in depth, using a carefully structured approach enhanced by numerous figures. In order to reinforce the concepts introduced and facilitate self-evaluation of design skills, the author includes problems with detailed solutions, as well as simulation exercises. Provides textbook coverage of the theory and design of operational amplifiers; Discusses low-voltage rail-to-rail input and output stages for design of low-power OpAmps; Presents frequency compensation techniques for all nine OpAmp configurations and compensation techniques for amplifiers with high capacitive loads; Includes design of µV-offset operational amplifiers and precision instrumentation amplifiers by applying chopping, auto-zeroing, and dynamic element-matching techniques. Provides beyond the rails CM input voltage ranges to OpAmps and InstAmps by the design of capacitive-coupled chopper input stages.